Peramalan Jumlah Siswa-Siswi Melalui Pendekatan Metode Regresi Linear - Trianggana, Dimas Aulia (Jurnal Media Infotama, 2020)
This application can predict data for the next academic year based on analysis of data from the previous academic year on the number of new student registrants per department. With the application, it can help the school in managing school quality assurance, so that it can attract interest from prospective students to register at the school based on the available majors. Based on the tests that have been carried out, it can be concluded that the functionality of the application is running as it should and the application is able to display forecasting results based on the trend data entered.